GETTING AROUND IN INDONESIA: SURVIVAL MOBILITY LITERACY NEEDS OF BASIC BIPA LEARNERS AND DIGITAL MULTIMODE COMIC RATIONALE - Fitri Febriyanti; Mochamad Whilky Rizkyanfi; Nuny Sulistiany Idris (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing number of BIPA (Indonesian as a Foreign Language), learners highlights the need for contextual and functional learning materials, particularly for beginner-level learners who face real life communication challenges in Indonesia. One essential competency is survival mobility literacy, which refers to the ability to communicate effectively in public transportation contexts. However, learning materials addressing this competency remain limited. This study aims to identify the difficulties and learning material needs of beginner-level BIPA learners related to survival mobility literacy and to formulate a design rationale for a digital multimode comic. A descriptive quantitative approach was employed, involving 15 basic-level BIPA learners from various countries through a questionnaire using a four-point Likert scale. The findings reveal that learners experience difficulties in using dialogues, asking questions, and understanding transportation-related vocabulary. The results also indicate strong preferences for contextual content, visual support, and digitally accessible materials. Based on these findings, a digital multimode comic is proposed as a theoretically and empirically grounded design framework for developing survival mobility literacy materials. This study contributes to the development of contextual, functional, and learner-centered BIPA teaching materials.